2000
DOI: 10.2169/internalmedicine.39.830
|View full text |Cite
|
Sign up to set email alerts
|

Acute Eosinophilic Pneumonia Following Cigarette Smoking.

Abstract: Twocases of acute eosinophilic pneumoniafollowing cigarette smoking are analyzed for characteristic features. The first patient noted dyspnea 14 days after initiation of smoking. The second patient noted dyspnea 12 days after beginning to smoke. Both cases had characteristic features including occurrence at an age younger than 30 years; less than 1 month duration of cigarette smoking before onset of disease ; and no identifiable cause of acute eosinophilic pneumoniaapart from smoking. Webelieve that acute eosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
40
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 15 publications
3
40
1
Order By: Relevance
“…Regarding peripheral eosinophilia, it is absent during the acute stage of AEP, but usually appears during the recovery stage. CS-AEP patients may also develop eosinophilia during the recovery stage, which has been reported in this issue (13). Although some investigators have reported a relationship between cigarette smoking and eosinophilia (15)(16)(17)(18)(19), it is not well knownthat cigarette smokecan induce acute eosinophilia.…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…Regarding peripheral eosinophilia, it is absent during the acute stage of AEP, but usually appears during the recovery stage. CS-AEP patients may also develop eosinophilia during the recovery stage, which has been reported in this issue (13). Although some investigators have reported a relationship between cigarette smoking and eosinophilia (15)(16)(17)(18)(19), it is not well knownthat cigarette smokecan induce acute eosinophilia.…”
mentioning
confidence: 58%
“…Although we first recognized and reported on CS-AEP, a number of cases must have previously gone unrecognized as such and thus unreported. Weagree with one of the conclusions of Shiota et al (13) that the high incidence in the literature ofAEP occurring within a month after initial cigarette smoking is not merely coincidental. …”
mentioning
confidence: 93%
See 2 more Smart Citations
“…24 The implication is that eosinophilic pneumonia is associated with cigarette smoking. [31][32][33][34] Indeed, it is very plausible that BAL may be useful for screening early or subclinical respiratory diseases among cigarette smokers. 35 Respiratory diseases are also associated with rheological properties of blood, which in turn constitute subclinical vasculopathy with known laboratory biomarkers and cigarette smoke.…”
Section: Implications For Respiratory Diseasesmentioning
confidence: 99%